Analisis Konsep Momen Gaya, Momen Inersia, dan Keseimbangan Benda Tegar pada Rumah Adat Osing Banyuwangi - Sholihah, Lailatus; Bekti Haryo Putri, Novita; Dina Handayani, Rif’ati (Jurnal Inovasi Pendidikan Sains dan Terapan (INTERN ), 2023)
The Osing Traditional House is the original traditional cultural architecture of Osing Banyuwangi which has existed since the 18-20 centuries until now. The Osing Traditional House was built based on traditional and hereditary function and philosophy values. Their knowledge of the Osing Traditional House so far is just a habit, even though what they applied in building the house contains a scientific concept. The purpose of this study is to examine the concept of moment of force, moment of inertia, and balance of rigid bodies in the Osing Traditional House. This research is a qualitative descriptive study using the Content Analysis method approach. Data collection is done by means of observation, interviews, and documentation. The data analysis technique is using content analysis with 6 stages namely Unitizing, Sampling, Coding, Reducing, Infering, Narrating). Based on the analysis results, in the components of the Osing traditional house, several physics concepts are found, namely the concept of moment of force, moment of inertia and balance. The concept of a stylistic moment in the Osing traditional house can be seen in the doors in the Osing traditional house. The moment of inertia in the Osing traditional house can be seen in the lower structure or the singing. The roof structure of the Osing Traditional House. If the log is at rest, then the log is in translational and rotational equilibrium. The results of this study are expected to explain the ethnoscience of the Oing Traditional House and can be a source of learning physics